The redevelopment of the Ninoy Aquino Parks and Wildlife Center based on the water infiltration capacity of urban trees - Alanano, Trishia Avril C.; Dul-loog, Vic L. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Approximately 48 percent of the Philippine's population currently lives in urban areas (World Bank, 2017). As more people continue to reside in these areas and the more rapid the pressure of urbanization becomes, the less green spaces are available for the general public. The underemphasize of green spaces becomes a problem as the availability of these spaces is an important element for the well-being and quality of life. Such spaces, including parks as one important component, provide numerous valuable ecosystem services to urban population including recreational opportunities, aesthetic enjoyment, and environmental function. This thesis focuses on raising the awareness of park users in order for them to provide support in further enhancing the ecosystem services provided by the Ninoy Aquino Parks and Wildlife Center. In order to do this, a survey was conducted to determine the level of awareness of park visitors and the degree of support that they are willing to provide. The survey results show only two percent are familiar with the term ecosystem services, and that the regulating value (water infiltration) of green spaces were valued on average at 50 percent importance. This then was used as a basis for the redevelopment of the park through the assessment of the trees' water infiltration capacity to determine which tree species are most suitable for the enhancement of the ecosystem services. Through the assessment, it was found that native tree species such as Pterocarpus indicus, Dillenia philippinensis and Peltophorum pterocarpum were most effective in its regulating services.
include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Parks -- Development; Parks -- Philippines